Validez de constructo y confiabilidad de la escala de satisfacción con la vida, en escolares de zonas rurales y urbanas de Cundinamarca = Construct validity and reliability of the Satisfaction with Life Scale, in schoolchildren from rural and urban areas of Cundinamarca - Hernández Mateus, Laura Vanessa
The aim of the present instrumental study was to determine the validity of the construct and reliability of the Satisfaction with Life Scale, in schoolchildren from rural and urban areas of Cundinamarca. The study involved the application of the scale on 258 schoolchildren from the city of Bogotá and the municipalities of Subachoque and Cogua, Cundinamarca, aged between 12 and 18 years of age (M = 15.03, SD = 1.219), carrying out exploratory and confirmatory factor analyses, as well as an analysis of reliability and internal consistency. The results show a unifactorial scale, which explains the 57.669% of the total variance, with said unifactorial model confirmed, a Cronbach's alpha of .814, positive correlations among all the reagents and between the items with the total of the scale, which allows us to conclude/state that the Satisfaction with Life Scale has adequate validity and reliability indexes to be used as a measure in schoolchildren in rural and urban areas of Cundinamarca.